Design of a novel bionic prosthetic knee joint. Issue 4 (5th September 2016) - Zhang, Xiufeng; Fu, Huiqun; Wang, Xitai; Li, Guanglin; Yang, Rong; Liu, Ying
Abstract : Purpose: This paper aims to find a new method that could be applied to the high and mid-grade prosthesis knee joint. Design/methodology/approach: Based on analysis, calculation, modeling, simulation and experimental study of the motion law of knee joint, this paper not only determines the structure and parameters of the knee joint and calculates the instantaneous center but also analyzes the stance stability and completes the optimization. With the help of experimental tests (fatigue test and gait curve test), the quality and performance of the designed knee joint is verified. Findings: The experimental results show that the gait curve of the designed knee joint is much closer to health people. The designed prosthesis knee joint, with adjustable swing speed and gait curve which are close to health limb, has a better performance when compared to the ordinary knee joint with four-bar linkage structure. Originality/value: This paper developed a prosthesis knee joint based on a novel design method that could be applied to the "high and mid" grade prosthesis knee joint and verified its function on an amputee performed the lower amputation, which could provide theoretical support for researches and designs related to prosthesis knee joint in future.